Feasibility of low fiber content PVA-ECC for jointless pavement application. (25th January 2021) - Arce, Gabriel A.; Noorvand, Hassan; Hassan, Marwa M.; Rupnow, Tyson; Dhakal, Nirmal
Highlights: ECC materials were developed incorporating low contents of non-oil-coated PVA fiber. Flexural fatigue performance of low fiber content ECC was evaluated. The response of low fiber content ECC pavements under traffic loading was assessed via FEM. Results suggest potential jointless functionality of low fiber content ECC pavements. Abstract: The objectives of this study were to: (1) develop and evaluate the properties of low fiber content Engineered Cementitious Composites (ECC) incorporating readily available ingredients (i.e., non-oil-coated PVA fiber, fine river sand, and Class F fly ash); and (2) evaluate the response of a low fiber content ECC material in pavement applications based on finite element analysis (FEA). Experimental results showed that reducing fiber content produced a decrease in the tensile strength and tensile ductility of ECC, which translated into a reduction of the flexural strength and deflection capacity of the composites; however, the compressive strength increased. Furthermore, increments in fly ash content caused an increase in the ductility of the composites; yet, the strengths (i.e., compressive, tensile, and flexural) were negatively affected. The modified restrained cracking potential parameter (Pm ) calculated for all ECC materials was highly negative suggesting the possibility of jointless pavement functionality. A low fiber content PVA-ECC material, M3-1.5%, was successfully developed and evaluated for pavement applications utilizing flexural fatigue testing and FEA. Flexural fatigue performance of M3-1.5% underperformed regular ECC; yet, substantially outperformed regular concrete. Furthermore, FEA results showed that the critical tensile stresses developed at the bottom of the low fiber content ECC pavements can be substantially reduced compared to those generated on regular concrete pavements due to its plastic deformation capability. In turn, this could mitigate the brittle failure of rigid pavements and allow for substantial thickness reduction.